Fish oil replacement by different microalgal products in microdiets for early weaning of gilthead sea bream (Sparus aurata, L.). Issue 5 (22nd August 2012) - Eryalçın, Kamil Mert; Roo, Javier; Saleh, Reda; Atalah, Eyad; Benítez, Tibiabin; Betancor, Monica; del, Maria; Izquierdo, Marisol
Abstract The aim of this study was to determine if algal products rich in DHA or ARA are able to completely replace fish oil in microdiets for marine fish larvae, gilthead seabream and if extra supplementation with EPA may further enhance larval performance. For that purpose, 20 day‐old gilthead seabream larvae of 5.97 ± 0.4 mm mean total length and 0.12 ± 0.001 mg mean dry body weight were fed with five microdiets tested by triplicate: a control diet based on sardine oil; a diet containing AquaGrow® DHA (diet DHA) to completely substitute the sardine oil; a diet containing AquaGrow® ARA (diet ARA); a diet containing both products, AquaGrow® DHA and AquaGrow® ARA to completely substitute the fish oil; and, a diet containing both products, AquaGrow® DHA and AquaGrow® ARA, together with an EPA source. Temperature, air and salinity activity tests were also performed to detect larval resistance to stress. At the end of the experiment, final survivals did not differ among groups. The microorganism produced DHA was able to completely replace fish oil in weaning diets for gilthead seabream without affecting survival, growth or stress resistance, whereas the inclusion of microorganism produced ARA did not improve larval performance. Moreover, addition of EPA to diets with total replacement of fish oil by microorganism produced DHA and ARA, significantly improved growth in terms of body weight and total length. The results of this study denoted the good nutritional value of microorganisms produced DHA as a replacement of fish oil in weaning diets for gilthead seabream, without a complementary addition of ARA. However, dietary supplementation of EPA seems to be necessary to further promote larval performance.